Análisis de Accesibilidad al Medio Físico para los estudiantes con discapacidad de la Universidad Nacional de Loja - Michelle Ximena, Camacho Rogel (2018)
The research work entitled "ANALYSIS OF ACCESSIBILITY TO THE PHYSICAL ENVIRONMENT FOR STUDENTS WITH DISABILITIES OF THE NATIONAL UNIVERSITY OF LOJA, is structured under the guidelines of Public Administration Career Research in accordance with the Regulation of Regime of the National University of Loja , the present consists of review of literature which exposes the theoretical basis related to all the knowledge of the subject, the part of results obtained in the collection of information through the different techniques used and the critical discussion of the facts to establish conclusions that entail to determine the recommendations. Its purpose is to analyze the current situation of the structure and physical environment of the National University of Loja in relation to the issue of accessibility for students with disabilities. To do this, it is important to identify the type of physical barriers students face on a daily basis that limits access to a comfortable, adequate and safe environment, then proceeded to establish punctually the effects caused by students with disabilities inaccessibility of the physical environment making problem-cause-effect relationship, ultimately determining the type of physical adaptations and infrastructure that should implement the National University of Loja by proposing in the research a graphic design based on the Ecuadorian Technical Norms of Accessibility of people with disabilities and reduced mobility to the physical environment, promoting in this way to guarantee the student with disability who is worthy and titu of rights to a quality education, permanence, mobility and graduation within this Institution of Public Higher Education.